The effect of portable HEPA filter air cleaner use during pregnancy on fetal growth: The UGAAR randomized controlled trial. (December 2018) - Barn, Prabjit; Gombojav, Enkhjargal; Ochir, Chimedsuren; Boldbaatar, Buyantushig; Beejin, Bolor; Naidan, Gerel; Galsuren, Jargalsaikhan; Legtseg, Bayarkhuu; Byambaa, Tsogtbaatar; Hutcheon, Jennifer A.; Janes, Craig; Janssen, Patricia A.; et al.
Abstract: Background: Fine particulate matter (PM2.5 ) exposure may impair fetal growth. Aims/objectives: Our aim was to assess the effect of portable high efficiency particulate air (HEPA) filter air cleaner use during pregnancy on fetal growth. Methods: The Ulaanbaatar Gestation and Air Pollution Research (UGAAR) study is a single-blind randomized controlled trial conducted in Ulaanbaatar, Mongolia. Non-smoking pregnant women recruited at ≤18 weeks gestation were randomized to an intervention (1–2 air cleaners in homes from early pregnancy until childbirth) or control (no air cleaners) group. Participants were not blinded to their intervention status. Demographic, health, and birth outcome data were obtained via questionnaires and clinic records. We used unadjusted linear and logistic regression and time-to-event analysis to evaluate the intervention. Our primary outcome was birth weight. Secondary outcomes were gestational age-adjusted birth weight, birth length, head circumference, gestational age at birth, and small for gestational age. The study is registered atClinicalTrials.gov (NCT01741051 ). Results: We recruited 540 participants (272 control and 268 intervention) from January 9, 2014 to May 1, 2015. There were 465 live births and 28 losses to follow up. We previously reported a 29% (95% CI: 21, 37%) reduction in indoor PM2.5 concentrations with portable HEPA filter air cleaner use. The median (25th, 75th percentile) birth weights for control and intervention participants were 3450 g (3150, 3800 g) and 3550 g (3200, 3800 g), respectively (p = 0.34). The intervention was not associated with birth weight (18 g; 95% CI: −84, 120 g), but in a pre-specified subgroup analysis of 429 term births the intervention was associated with an 85 g (95% CI: 3, 167 g) increase in mean birth weight. Conclusions: HEPA filter air cleaner use in a high pollution setting was associated with greater birth weight only among babies born at term. Highlights: Few randomized studies of air pollution and fetal growth haven been conducted. We evaluated the effect of portable HEPA air cleaner use during pregnancy on fetal growth. Air cleaners were not associated with fetal growth outcomes among all births. Among term births, air cleaners were associated with greater birth weight. Reducing air pollution may improve fetal growth.